Diffusion of plasticizer in a solid propellant based on hydroxyl-terminated polybutadiene - Juliano Libardi; Sergio P. Ravagnani; Ana M. F. Morais; Antonio R. Cardoso (Polímeros, 2010)
The aim of this work was to determine the dioctyl azelate (DOZ) plasticizer diffusion coefficient (D) for samples containing the interfaces of rubber, liner and solid composite propellant based on hydroxyl-terminated polybutadiene (HTPB). The samples used in the diffusion study were aged up to 31 days after the cure period at 80 °C. A computer program implementing a mathematical model of Fick's second Law of diffusion was developed to calculate the diffusion coefficient based on concentration data obtained from gas chromatographic analyses. The effects of the diffusion phenomenon were also investigated by Shore A hardness and scanning electron microscope (SEM) techniques. These analyses were carried out using samples aged at room temperature and at 80 °C. The hardness results showed an increasing trend for the samples aged at room temperature; however in the tests carried out at 80 °C they showed the opposite trend. The SEM analyses detected meaningful changes in the surface morphology of the propellant for both aging temperatures.